PENGARUH PENGGUNAAN APLIKASI YOUTUBE TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK AISYIYAH 14 PADANG - Latifah Mulya Hersa; Warlan Sukandar; Desmawati Roza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is grounded in the importance of social-emotional development in early childhood, an aspect that affects children's ability to interact socially, regulate emotions, and build relationships with others, amid the widespread use of the YouTube application among children. This study aims to determine the level of YouTube application use, the level of social-emotional development, and whether there is an influence of YouTube application use on the social-emotional development of children aged 5-6 years at Aisyiyah 14 Padang Kindergarten. This study used a descriptive quantitative approach with an ex-post facto causal comparative design. The research sample consisted of 24 children aged 5-6 years from classes B1 and B4. Data were collected through questionnaires completed by parents and classroom teachers, then analyzed using descriptive statistics, simple linear regression, and hypothesis testing. The results showed that the level of YouTube application use among children was generally in the low category (50.0%), while the level of children's social-emotional development was generally in the moderate category (95.8%). The regression test results showed an F value of 13.423 with a significance of 0.001 (< 0.05), so H1 was accepted, indicating a significant influence of YouTube application use on children's social-emotional development. The correlation coefficient (R) of 0.616 and the coefficient of determination (R Square) of 0.379 indicate that YouTube application use contributed 37.9% to the social-emotional development of children aged 5-6 years at Aisyiyah 14 Padang Kindergarten.